2009
DOI: 10.1021/jp907214a
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Structure of Cyclopentene Oxide and the Argon−Cyclopentene Oxide van der Waals Complex

Abstract: Rotational spectra of cyclopentene oxide and the argon-cyclopentene oxide van der Waals complex were studied using pulsed-jet Fabry-Perot Fourier transform microwave (FTMW) spectroscopy. Spectra of the parent along with those of the (13)C and (18)O singly substituted isotopologues, in natural abundance, of the monomer and of the complex were measured in the frequency region of 5-26.5 GHz. The complete heavy atom substitution structure was determined for the monomer and complex. The boat structure for cyclopent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The coordinates of argon resulting from this optimization of the complex are given in Table , labeled as Ar ( r e , ab initio). By placing the argon in a position that is analogous to the position we found with respect to the ring and epoxide group in cyclopentene oxide, the complex spectrum was predicted and easily fit. An assumption was made that the structure of the monomer species does not change upon complexation with argon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The coordinates of argon resulting from this optimization of the complex are given in Table , labeled as Ar ( r e , ab initio). By placing the argon in a position that is analogous to the position we found with respect to the ring and epoxide group in cyclopentene oxide, the complex spectrum was predicted and easily fit. An assumption was made that the structure of the monomer species does not change upon complexation with argon.…”
Section: Discussionmentioning
confidence: 99%
“…We had previously determined that the argon occupied a position above the ring and on the opposite side of the epoxide in the five-membered ring, cyclopentene oxide (CPO). 5 In the argon−cyclobutanone complex, 6 we found that the argon is not in van der Waals (vdWs) contact with the carbonyl carbon or oxygen. It is in contact with the relatively positively charged hydrogen on one of the cross ring carbons.…”
Section: ■ Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Microwave structural studies using numerous isotopologues of the monomer ring compounds and their rare gas complexes allow us to determine the site on the host ring at which the rare gas forms a van der Waals bond. We have determined that the argon occupies a position above the ring and on the opposite side of the epoxide in both the five-membered ring, cyclopentene oxide (CPO), 9 and the six-membered ring, cyclohexene oxide. 10 In the argon−cyclobutanone complex, 11 we found that the argon is in van der Waals (vdWs) contact with the carbonyl carbon but not the oxygen.…”
Section: ■ Introductionmentioning
confidence: 99%